Urgency of Silky Shark Protection In Bangka Belitung Province Based on International And National Law - Cahyaningtyas. S, Nur Asifah; Hutapea, Sintong Arion; Pamungkas, Wahyu Adi; Efriansyah, Muhammad Ezical (Tirtayasa Journal of International Law, 2023)
The silky shark is a fish that specializes in the pelagic zone and shallow waters that is currently in near-threatened status. This is due to the overexploitation of shark fishing. Exploitation activities carried out by fishermen cause environmental damage and also the extinction of the shark species itself. Bangka Belitung islands is one of the places where shark fishing and trade often occur, which should not be caught and protected by law. this research uses a normative method that is oriented with secondary data and source materials. the results of this study show that silky shark fishing in the islands of bangka belitung often occurs in terms of secondary data through conceptual approaches and legislative arrangements. Therefore, this research will discuss the importance of establishing shark protection both from the perspective of national law and international law that has been applied.